A humidity dose-CZM formulation to simulate new end-of-life recycling methods for photovoltaic laminates. (January 2022) - Liu, Z.; Reinoso, J.; Paggi, M.
Abstract: Humidity and temperature greatly influence the degradation of interfacial adhesion in photovoltaic (PV) modules. Besides, for an accurate prediction of the required energy to peel off the different plies of end-of-life PV laminates for recycling purposes, it is also essential to take these factors into account. A polynomial cohesive zone model (CZM) coupled with a humidity dose model is herein proposed to address these issues in the finite element (FE) framework. A novel three-dimensional interface finite element considering large deformation is adopted to accurately deal with the coupled material and geometrical nonlinearities involved in peeling tests. A consistent derivation and operator formulations for this interface finite element are detailed. Consistency between numerical predictions and peeling experimental results taken from the literature confirms the validity of the proposed approach. From the technical viewpoint, the numerical results show that peeling is energetically preferable over crushing to disassemble and recycle PV laminates at the end of their lifetime. The proposed modeling approach can effectively contribute to virtually design new methods for PV recycling. Highlights: A polynomial CZM coupled with humidity dose model. 3D large deformation interface finite element. Model validated by experimental results on accelerated hygrothermal tests. Assessment of efficacy of peeling for PV disassembling and recycling.